Approximate Solution of Time-Fractional Advection-Dispersion Equation via Fractional Variational Iteration Method - Birol İbiş; Mustafa Bayram (The Scientific World Journal)
This paper aims to obtain the approximate solution of time-fractional advection-dispersion equation (FADE) involving Jumarie’s modification of Riemann-Liouville derivative by the fractional variational iteration method (FVIM). FVIM provides an analytical approximate solution in the form of a convergent series. Some examples are given and the results indicate that the FVIM is of high accuracy, more efficient, and more convenient for solving time FADEs.